Economic and Political Foundations of Tax Structure - Hettich, Walter; Winer, Stanley L. (American Economic Review, 1988)
[The paper derives the essential elements of tax systems as the outcome of rational behavior in a model where government maximizes expected support and where opposition to taxation depends on the loss in full income. The analysis treats the level of expenditures as endogenous and integrates the influence of administration costs with that of political and economic factors. Tax structure is shown to be a system of related components in equilibrium.]